Why is John’s Apocalypse so Bloody?: John’s Use and Subversion of Combat Myths in Revelation 19:11–20:10 - Palmer, Edward T. (Tyndale bulletin, 2023)
The question of violence in John’s Apocalypse is a perennial issue producing numerous treatments with a variety of solutions. Nevertheless, very few of the many treatments seriously engage the combat myths of the ANE and how they may relate to the issue of violence in the Apocalypse. This lack of engagement is surprising given that the Apocalypse seems to draw from the plot elements, characters, and overarching concerns common to combat myths. This essay aims to rectify this by situating the Apocalypse within the combat myth tradition. When one does this, I argue that John’s use of the mythic pattern furnished by combat myths renders the violence of the Apocalypse intelligible while at the same time undermining the violent imagery with strategic departures and alterations.